Identification of a groES-like chaperonin in mitochondria that facilitates protein folding. - Lubben, T H (1990)
Mitochondria contain a polypeptide that is functionally equivalent to Escherichia coli chaperonin 10 (cpn10; also known as groES). This mitochondrial cpn10 has been identified in beef and rat liver and is able to replace bacterial cpn10 in the chaperonin-dependent reconstitution of chemically denatured ribulose-1,5-bisphosphate carboxylase. Thus, like the bacterial homologue, mitochondrial cpn10 facilitates a K(+)- and Mg.ATP-dependent discharge of unfolded (or partially folded) ribulose bisphosphate carboxylase from bacterial chaperonin 60 (cpn60; also known as groEL). Instrumental to its identification, mitochondrial cpn10 and bacterial cpn60 form a stable complex in the presence of Mg.ATP. Bacterial and mitochondrial cpn10 compete for a common saturable site on bacterial cpn60. As a result of complex formation, with either mitochondrial or bacterial cpn10, the "uncoupled ATPase" activity of bacterial cpn60 is virtually abolished. The most likely candidate for mitochondrial cpn10 is an approximately 45-kDa oligomer composed of approximately 9-kDa subunits. We propose that, like the protein-folding machinery of prokaryotes, mitochondrial cpn60 requires a cochaperonin for full biological function.